Energy renovation of Swedish single-family houses—a survey of barriers, drivers, and green loans - Niknafs, Pardis; Holmqvist, Gustav; Thollander, Patrik; Rohdin, Patrik (Frontiers in Energy Research, 2024)
According to the Energy Performance of Buildings Directive, 55% of the EU’s emission reductions will require renovations of the least efficient buildings. Therefore, it is important to gain a deeper understanding of how owners of single-family houses perceive energy efficiency measures, energy renovation, and barriers and drivers that influence their decision-making. Moreover, the homeowner’s perception of green loans is important, as one piece of the puzzle in how to finance these implementations. Swedish single-family houses account for 40% of residential energy use and 45% of heated area, and they are mostly privately owned. These decision-making processes are, to a large degree, unknown, as the main focus has been on professional actors and tenants, not on single-family and privately owned buildings. This paper presents the perspective of these owners and discussions related to their decision-making. It is therefore important to evaluate the barriers and drivers involved in this decision-making process from the perspective of house owners, and to include socio-economic factors as well as the potential for green loans. This study includes single-family house owners in two cities of different sizes who responded to a survey regarding their perspectives on energy renovation. The results showed that homeowners with lower incomes were more neutral about barriers to energy renovation. In contrast, house owners with higher incomes, and those who moved into their houses more recently, prioritized other types of renovations and investment over energy renovations. According to households where the respondents were over 60 years old, barriers such as lack of capital and time are not perceived as significant barriers to energy renovation. Moreover, this study showed that households with younger owners, those who moved recently to their homes, and those with higher incomes, are more likely to take loans for energy renovations. For these younger households and those who moved into their houses relatively recently a window of opportunity could therefore be identified, where tailored policies can be targeted toward the sector when houses are recently sold. In all cases, except for those over 70 years, respondents stated that green loans increased their interest in energy efficiency investments.